Perancangan Busana Panggung Anak dengan Sumber Ide Bunga Matahari - Hesty Agustina; Ruth Ambarsari; Salim Salim (Texture:Art and Culture Journal, 2023)
This final project takes sunflowers as a source of ideas to be developed into designs and then realized in the form of children's clothing using tapestry, knitting, and pattern magic techniques, in order to explore techniques in developing sunflower motifs in 3D clothing. For the purpose of using the source of the idea of sunflowers because sunflowers themselves are a depiction of optimism and joy that are suitable for the concept of children's clothing. The method used in the process of creating this fashion work is through design exploration (concepts, determination of the chosen concept then design development from the concept, determination of the selected design, experimental techniques used, determination of the right technique from experiments), execution of works (pattern making, pattern cutting, etc.) making tapestry, laying patterns on fabrics, cutting fabrics, sewing processes, and finishing. The final product is three stage children's clothing with artsy style that uses a combination of tapestry and knitting techniques and the use of ATBM lurik fabrics as traditional fabrics. The choice of lurik cloth in this work is due to the appreciation and respect for traditional Indonesian fabrics and their motif were many variations.